Wedding in Bojonegoro in Al-‘Urf and Al-Maslahah Al-Mursalah (Phenomenological Study of Walimah Al-‘Urs Community in Pohwates Village, Kepohbaru District, Bojonegoro Regency) - Abdullah, Zidni; Ihsan, Abid Miftakhul (Journal of Transcendental Law, 2023)
This research discusses Wedding in Bojonegoro in Al-‘Urf and Al-Maslahah Al-Mursalah (Phenomenological Study of Walimah Al-‘Urs Community in Pohwates Village, Kepohbaru District, Bojonegoro Regency). The purpose of this research is to answer the formulation of the problem: 1). How is the obligation to carry out walimah al-‘urs in the community of Pohwates Village, Kepohbaru District, Bojonegoro Regency?; 2). How is the strategy of implementing walimah al-‘urs (wedding) in the community of Pohwates Village, Kepohbaru District, Bojonegoro Regency?; 3). How is the impact of walimah al-‘urs on the wedding of the people of Pohwates Village, Kepohbaru District, Bojonegoro Regency? This research is a field research with qualitative methods. Data collection and research methods through direct interviews with respondents at the place of observation. All research data is collected and studied then analyzed descriptively analytically with a deductive mindset. The results of this study state that the practice of walimah al-‘urs which must be carried out by the people of Pohwates Village with luxury and festivity costs a lot of money, the minimum nominal that must be spent is IDR 41,000,000. The strategy taken to ease the burden of sahib al-hajah is in the form of arisan, buwuhan as debt, the implementation of walimah al-‘urs at harvest time, seserahan (Offerings given by the groom to the bride) with large and plentiful amounts. Walimah al-‘urs has a positive impact on the local community, namely, adding value to the sacredness and solidity of the household to maintain and preserve culture, strategies that appear to help, entertain, give a good name. While the negative impacts are the reduction in the practice of walimah al-‘urs in accordance with Islamic guidance, wasteful, delaying marriage continuously so that it can reduce productivity, increasing the risk of disorders in children, decreasing youth interest in marriage and the burden caused by debt and arisan.